Antenna design for pineapple moisture content - Abdulhakim Warsame, Abdirahim (2021)
An E shape microstrip patch sensor, pineapple moisture content was measured. E-shape patch sensor operating at 2.4GHz developed on FR4 substrate with 4.3 permittivity and 1.6mm thickness. The sensor operates at a frequency range of 2.4GHz. as part of the simulation, CST software was used to measure the moisture effect on the antenna a rectangular substrate was deployed with permittivity that matched with the desired Moisture content which is pineapple in our case, furthermore by choosing the right dielectric we can also reduce the propagation of surface waves using media. Thus, substrates dielectric constant and loss tangent can affect the performance parameters (S11, VSWR, gain and directivity) on an antenna element. A deep analysis is performed on a microstrip patch antenna. The Pineapple box permittivity change the frequency shifting, when a higher permittivity moisture content is placed on the top of antenna, it will shift the frequency response towards higher frequency band. It means more Moisture content then more frequency shifting where the sensor permittivity is defining the moisture content, Higher permittivity means more content of moisture within the sensor and low permittivity denotes low moisture content.